Монгол Улсын Засгийн газар орос зөвлөх түшмэлтэй болсон түүх - Г. Цэнджав (Politology, 2023)
After Mongolia has announced its independence of national freedom on the 29th day of December, 1911, our country had started putting forward proposals to the neighboring and third countries to cooperate mutually efficiently and peaceably in order to strengthen its independence. But exclusively only Russia had applied the active position on activities and policy on Mongolia. According to request of power holder rulers of Mongolia the Russian Government had started taking different kinds of measures gradually in order to resolve loan and aid issues in their favor. In this article the issues about how the Russian government created new position of an Russian advisor for the Mongolian Government, how they started to control Mongolian economic resources through those officials, how they constrained the powerful influence of Chinese economics gradually and penetrated a number of Russian research expeditions to Mongolia in order to create their monopoly. Also this article is included the materials related to actions conducted by S.A. Kozin.